Digitalization of Environmental Information in the Republic of Kazakhstan: Issues of Legal Regulation - YERKINBAYEVA, Lazzat; NURMUKHANKYZY, Daniya; KALYMBEK, Bakytzhan; OZENBAYEVA, Aigerim; KALYMBEKOVA, Zhanna (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
This article considers legal regulation in the sphere of digitalizing environmental information. The study addresses the legislative consolidation of such digitalization to protect the environment and use natural resources, as well as respect human rights to access environmental information. The article is based on both general and special scientific methods. The article provides recommendations on improving the existing legislation in the field of access to environmental information and regulating the digitalization of environmental information.